2007
DOI: 10.1002/ijc.22693
|View full text |Cite
|
Sign up to set email alerts
|

Role of S128R polymorphism of E‐selectin in colon metastasis formation

Abstract: The extravasation of cancer cells is a key step of the metastatic cascade. Polymorphisms in genes encoding adhesion molecules can facilitate metastasis by increasing the strength of interaction between tumor and endothelial cells as well as impacting other properties of cancer cells. We investigated the Ser128Arg (a561c at the nucleotide level) polymorphism in the E-selectin gene in patients with metastatic colon cancer and its functional significance. Genotyping for a561c polymorphism was performed on 172 can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…The most compelling evidence for the role of E‐selectin polymorphism in malignancy comes from previous genotype and allele frequencies' studies showing that this specific polymorphism is associated with the susceptibility to metastasis formation in colon cancer 26, 27. In the current study, we attempted to determine whether an association exists between this E‐selectin gene variant and pancreatic cancer.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The most compelling evidence for the role of E‐selectin polymorphism in malignancy comes from previous genotype and allele frequencies' studies showing that this specific polymorphism is associated with the susceptibility to metastasis formation in colon cancer 26, 27. In the current study, we attempted to determine whether an association exists between this E‐selectin gene variant and pancreatic cancer.…”
Section: Discussionmentioning
confidence: 97%
“…In general, genetic polymorphisms in leukocyte‐ and endothelial‐cell‐adhesion molecules have been defined and studied extensively in diseases with multifactorial etiology, such as premature coronary artery disease, non‐insulin‐dependent diabetes mellitus, and atherosclerosis 14, 16, 19–25. The role of S128R polymorphism of E‐selectin has been studied in colon cancers, but no information is currently available on pancreatic cancer 26, 27.…”
Section: Introductionmentioning
confidence: 99%
“…The S 128 R polymorphism of the E-selectin gene is of interest for two reasons: first, it is overrepresented in certain patient groups affected by disease that is characterized by an increased adhesiveness of leukocytes to the endothelium; such as atherosclerosis and myocardial infarction and secondly, it is a functional polymorphism since it modifies ligand affinity 5,6. This mutation confers an alteration in selectin ligand-binding specificity which leads to a gain of function under flow conditions, possibly amplifying the number of leukocytes that roll and subsequently adhere to the endothelium 7.…”
Section: Introductionmentioning
confidence: 99%
“…On analysing the genotypic differences of ischemic stroke and hemorrhagic stroke in the study population, we found significant difference between AC genotype (p = 0.01) and C allele (p = 0.001) between the two stroke types. The S128R functional polymorphism is known to be overrepresented in certain patient groups and leads to amplification in the number of leukocytes adhering to the endothelium [17,18,31]. Such activated endothelial cells support more rolling of neutrophils and mononuclear cells when compared with cells transduced with wild type E-selectin [35].…”
Section: Discussionmentioning
confidence: 97%
“…This makes the cytokine inducible cell surface glycoprotein E-selectin, an attractive gene to study variation in inflammatory responses and its severity associated with stroke. The E-selectin (S128R) polymorphism is of major interest because it is a functional polymorphism, which modifies ligand affinity and also causes increased adhesiveness of leukocytes to the endothelium in atherosclerosis and myocardial infarction [17,18].…”
Section: Introductionmentioning
confidence: 99%